Hubungan Perceived Organizational Support dengan Intensi Turnover pada Karyawan Usia Dewasa Awal di Bank X - Paramita Indraswari; Semiati Ibnu Umar; Andi Supandi (Fakultas Psikologi Universitas Pancasila, 2010)
Studies show that perceived organizational support correlates with turnover intention, but the correlation figure varies depending on the nature of the work. This study aims to examine the relationship between perceived organizational support and turnover intention on bank employees at the X bank. Perceived Organizational Support (POS) variable is measured with scale developed by Eisenberger et al. (1986) through Survey of Perceived Organizational Support (SPOS). Turnover intention variable is measured with withdrawal cognition scale developed by Tang, Kim, and Tang (2000). Participants of this study are 64 employees of X bank, aged 18-40 years old, holding at least bachelor degree and having been working for one year. The result generates a correlation value of -0.286, showing that there is a relationship between perceived organizational support and turnover intention on young adult employees of X bank.